2022
DOI: 10.1542/hpeds.2021-006464
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Care For Critically Ill Children Beyond Hospital Discharge: Current State of Follow-up

Abstract: OBJECTIVES: Survivors of the PICU face long-term morbidities across health domains. In this study, we detail active PICU follow-up programs (PFUPs) and identify perceptions and barriers about development and maintenance of PFUPs. METHODS: A web link to an adaptive survey was distributed through organizational listservs. Descriptive statistics characterized the sample and details of existing PFUPs. Likert responses regarding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…This timeline therefore suggests that post-discharge behavioral health follow-up for PICU patients is critical. While follow-up clinics for adult ICU survivors have existed for decades [ 113 ], similar programs are rare for PICU survivors [ 114 ], with the few existing programs embedded within larger children’s hospital systems. Of the PICU follow-up clinics that have been described in the literature, only 12% included a psychologist team member and one in three programs were physician only [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This timeline therefore suggests that post-discharge behavioral health follow-up for PICU patients is critical. While follow-up clinics for adult ICU survivors have existed for decades [ 113 ], similar programs are rare for PICU survivors [ 114 ], with the few existing programs embedded within larger children’s hospital systems. Of the PICU follow-up clinics that have been described in the literature, only 12% included a psychologist team member and one in three programs were physician only [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…While follow-up clinics for adult ICU survivors have existed for decades [ 113 ], similar programs are rare for PICU survivors [ 114 ], with the few existing programs embedded within larger children’s hospital systems. Of the PICU follow-up clinics that have been described in the literature, only 12% included a psychologist team member and one in three programs were physician only [ 114 ]. Most mainly provided screening for psychological morbidity and behavioral health care services for children after their PICU stay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current PICU follow-up programs (11)(12)(13)(14)(15)(16)(17) vary widely with respect to, among others, the included patients, involved health care professionals, follow-up moment(s), and assessed outcomes. Moreover, most PICU follow-up programs lack structured data collection (11), which is essential for health care evaluation and scientific research on outcome and prognosis of critically ill children. Defining features of our structured multidisciplinary PICU follow-up program include the following: 1) a multidisciplinary team that is responsible for patient follow-up, 2) structured follow-up using evidence-based protocols and well-defined inclusion and exclusion criteria for follow-up, 3) the use of a one stop shop format for consultations, with consultations of all health care professionals scheduled consecutively, 4) the use of online questionnaires on physical and psychosocial functioning to prepare for the consultations, 5) structured data collection using discrete registrations, 5) yearly health care evaluation sessions aimed at improving the standard of care during and after PICU admission, and 6) the use of outcome data for scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…Only 14% percent of the respondents reported a follow-up program, this seems low but goes in line with other observations. Williams et al found in an US focused survey on PICU follow-up programs that 35% of the responding PICUs had a program in place of which only about one quarter was broadly inclusive to a wide range of PICU patients ( 27 ). What follow-up after pediatric intensive care should look like in our health system remains unclear.…”
Section: Discussionmentioning
confidence: 99%